Service-learning (SL): A case study of challenges faced by learners at a private higher learning - Soo, Elaine Jia Xuan; Lee, Chia Suen; Leong, Chai Yan; Lin, Fan Hui (2023)
This study is committed to filling in the gaps in our knowledge of the challenges that stand in the implementation of service-learning (SL) for students at private universities. By recognizing challenges that exist, the research intended to increase the quality of service learning and improve student engagement and learning outcomes. The findings of the research contributed to the field of SL by providing valuable insights that can inform decision-making and drive positive change within the education system, ultimately improving the quality of SL and student learning outcomes at Universiti Tunku Abdul Rahman (UTAR). Hence, this research explored the concept of service-learning among Universiti Tunku Abdul Rahman (UTAR) learners and identified the challenges they faced. The findings revealed three aspects of SL, including experiential learning, academic requirement, and community service while the students faced obstacles including time constraints, miscommunication, personal issues, lack of support, and competition throughout the SL implementation. The implications of the study call for increasing student, faculty, and administrative awareness of SL at UTAR, resolve the obstacles learners encounter when participating in SL activities, develop policies that promote and support SL in higher education institutions, and informing the development of service-learning theories and concepts. The study was limited by the inability to interview community members involved in service-learning programs and the exclusion of UTAR educators from the interview process